A left approach to development - Patnaik, Prabhat (2010)
Against the "means-based approach" to development that the bourgeoisie projects, the left must project a "rights-based approach". Since "rights" are guarantors of welfare gains, every winning of rights likewise strengthens them. The acquisition of rights on the part of the people, including rights to minimum bundles of goods, services and security, amounts therefore to winning crucial battles in the class war for the transcendence of capitalism. If the left were to put on its agenda a struggle for people's rights and adopt a rights-based approach to development as opposed to the means-based approach of the bourgeois formations, it would not constitute a retreat into abstract humanism but would be an integral part of the dialectics of subversion of the logic of capital. - Reproduced.
Keywords: Economic and social development